2015
DOI: 10.1037/pac0000092
|View full text |Cite
|
Sign up to set email alerts
|

Gender perceptions and support for compromise in the Israeli-Palestinian conflict.

Abstract: The goal of our study was to explore factors that underlie public support for compromise in protracted, asymmetrical conflict. We introduce a gendering for compromise model in which, in line with previous studies (Maoz & McCauley, 2008), support for compromise is determined by perception of threat from the opponent. However, innovatively, our model also presents perception of the opponent as having stereotypical feminine traits as an important predictor of willingness to compromise in conflict. This model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The correlation between the 12% of the participants who indicated they trust the Palestinian leader and the 12% who perceived the news item as reliable suggests that prior real-world knowledge, rather than the textual design, could have affected the participants’ judgments and pushed them to react to Abbas’ decision with a highly skeptical attitude. In addition, the data conformed with previous studies (David and Maoz, 2015; David et al, 2018) and indicated that Jewish-Israelis express a medium level of support for political compromise ( M = 3.23, SD = 1.51), with 38% of the participants supporting a possible peace initiative (ratings of 4, 5 or 6 on the 1–6 scale). In contrast to the issue of trusting the proposing leader, the reliability of the news item had no significant influence on support for political compromise.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The correlation between the 12% of the participants who indicated they trust the Palestinian leader and the 12% who perceived the news item as reliable suggests that prior real-world knowledge, rather than the textual design, could have affected the participants’ judgments and pushed them to react to Abbas’ decision with a highly skeptical attitude. In addition, the data conformed with previous studies (David and Maoz, 2015; David et al, 2018) and indicated that Jewish-Israelis express a medium level of support for political compromise ( M = 3.23, SD = 1.51), with 38% of the participants supporting a possible peace initiative (ratings of 4, 5 or 6 on the 1–6 scale). In contrast to the issue of trusting the proposing leader, the reliability of the news item had no significant influence on support for political compromise.…”
Section: Methodssupporting
confidence: 88%
“…Support for political compromise was based on three questions (adapted from David and Maoz, 2015; David et al, 2018; Shamir and Shikaki, 2010) that were rated on a 6-point scale ranging from strongly disagree (1) to strongly agree (6). Responses to the three items were averaged for each respondent to create one scale according to which a high score means high support for political compromise.…”
Section: Methodsmentioning
confidence: 99%
“…However, when cultures were perceived as feminine, such messages activated among men a sense of moral obligation for altruism. In another study, David and Maoz (2015) found that perceiving out-groups as having stereotypical feminine traits (POSFT) and lower perception of threat from Palestinians predict increased levels of support for compromise. In the current study, we wish to further examine collective gender constructions by investigating how perceiving one's own group as having feminine-empathic traits (POFET), rather than perceptions of the out-group, and levels of empathy to the out-group are associated with support for political compromise with the out-group.…”
Section: Gender-empathic Constructions and Support For Compromisementioning
confidence: 96%
“…Within the fast-growing literature on gender, conflicts, and negotiation, accumulated evidence shows the effect of gender and gender-related expectations and perceptions on political attitudes concerning conflicts, such as support for militant actions and compromise (David and Maoz 2015; David et al 2016; Eichenberg 2003; Maoz 2009; Tessler and Warriner 1997). The affective social role of women as empathic and other concerned is suggested as a possible factor that can explain the gender-related difference with regard to negotiation (Olekalns 2014; Pelligra 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation